2015
DOI: 10.1007/s11430-014-4998-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different deformation mechanisms on the chemical structure of anthracite coals

Abstract: To study the effect of different deformation mechanisms on the chemical structure of anthracite coals and further understand the correlation between changed chemical structures and coal and gas outburst, ten groups of sub-high-temperature and sub-high-pressure deformation experiments were performed. All samples maintained primary structure, which were collected from the Qudi Mine in the southern Qinshui Basin of China. The samples were analyzed by ultimate analysis, Vitrinite Reflection (VR), Fourier Transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Frictional heat generated by fault motion could lead to early-metamorphism of coal containing the degradation of oxygen functional groups [41,130,131]. According to recent research, strong ductile deformation in zone I could also change the molecular structures of coal by transformation into strain energy [39,40,132]. Besides, the higher R o,max of sample 3 also indicated that the maturation degree of sample 3 was advanced by the influence of stress-induced dynamic metamorphism, including the stress degradation of functional groups (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frictional heat generated by fault motion could lead to early-metamorphism of coal containing the degradation of oxygen functional groups [41,130,131]. According to recent research, strong ductile deformation in zone I could also change the molecular structures of coal by transformation into strain energy [39,40,132]. Besides, the higher R o,max of sample 3 also indicated that the maturation degree of sample 3 was advanced by the influence of stress-induced dynamic metamorphism, including the stress degradation of functional groups (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been reported that there is early metamorphism of coal molecular structures in TDCs [37,38]. Side chains in TDCs including aliphatic structures and functional groups are disassociated by tectonic stress, which is followed by aromatic structures being collaged and rearranged (especially in ductile deformed coal) [39,40]. Furthermore, relevant studies have shown that coal molecular structures around faults are altered by strong deformation and frictional heat [41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…8 Under the external force, coal breaks and a large number of cracks generated. Consequently, coal molecules would be destroyed, generating a large number of free radicals, [42][43][44][45] The new radical reacts with oxygen:…”
Section: Mechanism Of Coal Spontaneous Combustionmentioning
confidence: 99%
“…Using EPR, researchers found that more free radicals were induced through bond cleavages under stress/mechanical force [24,[44][45][46]. The FTIR and 13 C NMR results revealed that compared with the adjacent primary coals, tectonically deformed coals (TDCs) had lower aliphatic carbons and higher aromatic carbons [47][48][49][50][51]. Since TDCs and the primary coals were sampled from adjacent areas, they are assumed to have gone through the same thermal evolution, and the difference between them are thought to be the influence of stress.…”
Section: The Relationship Between Stress and Coalificationmentioning
confidence: 99%
“…The related work of Hou and co-workers has just been reviewed by Dong et al [66]. Different gases were collected in the experiments and corresponding chemical structure changes were revealed by elemental analysis [64], FTIR [51,64,65], and 13 C NMR [65] at temperatures lower than the pyrolysis needed. Though deformation experiments were performed by different researchers, they face the same problem how to prove the gases are generated during deformation and not from desorption.…”
Section: The Relationship Between Stress and Hydrocarbon (And Nonhydrmentioning
confidence: 99%